Secure Sensitive Services Composition in Edge and Cloud Environment - Alenezi, Khaled Aladham; Hamdi, Hedi (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Secure service composition in edge and cloud environments is a challenging task, due to the need to consider factors such as cost, location, sensitivity of the processed data, and trust level. This paper proposes a novel secure service composition approach that addresses these challenges. The proposed approach calculates a weighted rating for each service, based on its rating, trust level, and the sensitivity of the data it will process. The highest weighted rating services are then selected to form the service composition. The proposed approach has been evaluated using a generated dataset of edge and cloud services. The results show that the approach is able to select secure service compositions by considering important factors like: Service rating, Trust level, Sensitivity of the processed data and user needs, by considering all of these factors the proposed approach is able to select secure service compositions that meet the user’s needs while also ensuring the security of the data. The proposed approach can be used to enhance the security of service composition in a range of applications, including cloud computing, business process management, and the Internet of Things. It is particularly useful in edge and cloud environments where sensitive data is processed, this is because the proposed approach takes into account the sensitivity of the data when selecting services. For example, in a cloud-based healthcare application, the proposed approach can be used to select secure services for storing and processing patient data. This can help to protect patient privacy and security. In a Business Process Management workflow for processing financial transactions, the proposed approach can be used to select secure services for authenticating users and authorizing transactions. This can help to prevent fraud and financial loss. In an Internet of Things application for monitoring industrial equipment, the proposed approach can be used to select secure services for collecting and analyzing data from sensors. This can help to protect the industrial equipment from cyberattacks. Overall, the proposed approach is a flexible and effective solution for secure service composition in edge and cloud environments. It can be used to enhance the security of a wide range of applications, particularly those that involve the processing of sensitive data.